Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1159/000091091
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Estimation in Children Using Auditory Steady-State Responses to Multiple Simultaneous Stimuli

Abstract: Objective: It was the aim of this study to explore the use of auditory steady-state response (ASSR) to multiple simultaneous stimuli for threshold estimation in young children. Method: The subjects consisted of 40 children, aged from 6 months to 5 years, with variant degrees of sensorineural hearing loss. Simultaneous tonepips (0.5, 1, 2 and 4 kHz) with an amplitude modulated at different rates from 77 to 103 Hz were presented to both ears by insert phones. All children were tested with ASSR and age-appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
6
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 30 publications
10
53
6
2
Order By: Relevance
“…It is important to point out that despite this study compare ASSR with PTA and not with VRA (Visual Reinforced Audiometry) and/or conditioned audiometry that are used with infant and preschoolers the finding were similar (11,12,13,16,14,15,16) in what refers to the strong correlations of VRA and/or conditioned audiometry and ASSR to sensorial hearing losses, with larger differences between thresholds in mild hearing losses (11,12) and smaller on the more severe ones (12). However, no study with an analysis similar to the one presented in this research was found on the literature.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is important to point out that despite this study compare ASSR with PTA and not with VRA (Visual Reinforced Audiometry) and/or conditioned audiometry that are used with infant and preschoolers the finding were similar (11,12,13,16,14,15,16) in what refers to the strong correlations of VRA and/or conditioned audiometry and ASSR to sensorial hearing losses, with larger differences between thresholds in mild hearing losses (11,12) and smaller on the more severe ones (12). However, no study with an analysis similar to the one presented in this research was found on the literature.…”
Section: Discussionmentioning
confidence: 78%
“…In cases of sensorial hearing losses the thresholds determined by the ASSR has shown strong correlations with behavioral thresholds determined by the Visual Reinforcement Audiometry (VRA) and/or conditioned audiometry (6,11,12,13,14,15,16), as well as by the pure tone audiometry (PTA) (17,18,19,20,21). In what refers to the degree of sensorial hearing loss the studies show weaker correlations with the less severe losses (22,7,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers 20 observed a high correlation between the ASSR and behavioral thresholds throughout the study sample including children with sensorineural hearing loss. Research with children with sensorineural hearing loss demonstrated that, although the mean difference between the ASSR and the behavioral assessment was 8 to 15 dB, being higher for the ASSR, there was a strong correlation between the two procedures 21 . Thus, the findings of the present study disagree with the aforementioned studies, and it is believed that because the children in the studied sample presented conductive hearing loss, increasing the differences between the behavioral and electrophysiological evaluation due to the greater instability of the responses to the conductive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…This information is related to the type of hearing loss, if conductive or sensorineural, and those necessary for the differential diagnosis of the hearing neuropathy. 13,15,26 For this reason, we deemed important to use the click-BERA and the SSEAP together, in such a way that one completes and confirms the information of the other; by the same token, logoaudiometry is used to confirm pure tone thresholds, as suggested by Cone-Wesson et al 22 We must also stress that some studies have suggested that the decisions about referring a patient to cochlear implant are reinforced with the SSEAP, as well as the decision about which ear will be implanted. 8,10,23 In fact, although the SSEAP were not routinely done in clinical practice, and even considering that this study is experimental, these potentials add important information.…”
Section: Discussionmentioning
confidence: 99%